A CASE REPORT: OSTEOPOIKILOSIS WITH UNDIFFERENTIATED CONNECTIVE TISSUE DISEASE, LIVEDOID VASCULITIS AND ANTIPHOSPHOLIPID SYNDROME - Alev Kazancı; Şebnem Ataman; Nurben Süldür; Mesut Birol Atay (Archives of Rheumatology, 2002)
Osteopoikilosis, which belongs to the group of osteosclerotic diseases, has an autosomal dominant inheritance. Having typical radiological findings and asymptomatic clinical course, 15-20% of cases may experience mild articular tenderness and effusions. Osteopoikilosis associated with a connective tissue disease and/or livedoid vasculitis and/or antiphospholipid syndrome has not been reported yet. Here, a patient with undifferentiated connective tissue disease, livedoid vasculitis, antiphospholipid syndrome and osteopoikilosis will be discussed.